Estranged: Notes on the Historical Development of the Relationship between Players and Manufacturers of Ice Hockey Equipment in Canada. Issue 1 (27th April 2022) - Nothen, Guilherme; Kidd, Bruce
Abstract: This inquiry seeks to address the historical development of the relationship between players and manufacturers of ice hockey equipment in Canada. It pays particular attention to three inter-related trends that have affected this relationship quite decisively. First, the monopolization of equipment standards, enabled by a convergence in the interests of emerging equipment companies and hockey leagues, as the hockey manufacturing industry consolidated a solid Canadian presence throughout the twentieth century. Second, the rise of offshoring and outsourcing strategies, which set in motion a wave of factory closures and layoffs – culminating in the rather paradoxical fact that, today, almost the totality of the ice hockey equipment consumed in Canada was produced in foreign lands. Finally, the article presents what research participants perceive as a significant change in the profile of the executives who run major hockey manufacturing companies, namely the replacement of those with direct hockey experience by financial experts. The study concludes that, together, these three trends combined to drive players and manufacturers of ice hockey equipment progressively apart. The piece closes with a brief analysis of the present situation as it relates to the hockey manufacturing industry in North America.